Analisis Pemahaman Konsep Matematika Siswa dalam Menyelesaikan Soal Word Problem Tipe Hots Ditinjau dari Gaya Kognitif - Ira Apriliani Widyastuti; FX Didik Purwosetiyono; Muhammad Saifuddin Zuhri (Journal on Education, 2024)
Students' problems in understanding mathematical concepts to solve word problems of the hots type became the background of this study. The purpose of this research is to determine the ability to understand mathematical concepts of students with a cognitive style in solving hot type word problems. The population used in this study were students of SMP Negeri 2 Karangawen. While for the withdrawal of samples using purposive sampling technique the sample was taken from 26 student namely 2. This study used qualitative research methods which in its implementation used observation, tests, and interviews. Data analysis is carried out interactively and takes place continuously and through 3 stages, namely data reduction, data presentation, and conclusion drawing. The results revealed that subjects who have a reflective cognitive style have a better concept understanding ability in problem solving HOTS model questions, compared to students with impulsive cognitive style. Therefore, it is important for students to practice HOTS model problems in order to improve good concept understanding.